2019
DOI: 10.1101/gr.246884.118
|View full text |Cite
|
Sign up to set email alerts
|

Circadian gene variants and the skeletal muscle circadian clock contribute to the evolutionary divergence in longevity across Drosophila populations

Abstract: Organisms use endogenous clocks to adapt to the rhythmicity of the environment and to synchronize social activities. Although the circadian cycle is implicated in aging, it is unknown whether natural variation in its function contributes to differences in lifespan between populations and whether the circadian clock of specific tissues is key for longevity. We have sequenced the genomes of Drosophila melanogaster strains with exceptional longevity that were obtained via multiple rounds of selection from a paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 115 publications
3
27
0
Order By: Relevance
“…We recently found that the muscle transcriptome and proteome become progressively disconnected with aging in Drosophila 8 . By comparing the changes induced by UBR4 loss at the transcript level versus the protein level, we found an overall low correlation ( r 2 = 0.207) at 6 months of age, as expected based on the molecular function of UBR4, which is a ubiquitin ligase that modulates the degradation of target proteins, independently from their mRNA levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently found that the muscle transcriptome and proteome become progressively disconnected with aging in Drosophila 8 . By comparing the changes induced by UBR4 loss at the transcript level versus the protein level, we found an overall low correlation ( r 2 = 0.207) at 6 months of age, as expected based on the molecular function of UBR4, which is a ubiquitin ligase that modulates the degradation of target proteins, independently from their mRNA levels.…”
Section: Resultsmentioning
confidence: 99%
“…Muscle functional assays were done as before 8 . In brief, flight capacity was assessed by releasing flies into a clear box and counting the number of flies that could fly and that could not (i.e., that dropped immediately downward) to derive the percentage of flies not flying.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissues from Drosophila and mice of the desired genotypes and ages, and treatment of HKE293 cells and human brain organoids should be done according to the specific experimental requirements and following procedures as described in our and other recent studies ( Hunt et al., 2019a ; Hunt et al., 2021 ; Hunt et al., 2019b ; Hunt et al., 2015 ; Rai et al., 2021 ). Once obtained, these tissues can be examined following the procedures described below.…”
Section: Before You Beginmentioning
confidence: 99%
“…Whereas, the aging is characterized by disruption on circadian rhythms, the opposite is true too. The chronic deraignment on circadian clock reduces the longevity on Drosophila [ 38 , 39]. In humans, the shift-workers show loss of circadian rhythms and consequently higher risk to develop metabolic abnormalities and early aging observed by shorter of leukocytes telomere length [ 40 ].…”
Section: Aging and Circadian Rhythms Disruptionmentioning
confidence: 99%